2019
DOI: 10.3126/jfstn.v11i0.29690
|View full text |Cite
|
Sign up to set email alerts
|

Study on Chemical and Bioactive Components of Different Floral Sources’ Honey in Nepal

Abstract: Honey samples of commercial honey bee (Apis mellifera) were collected from different bee keepers in Nepal. Total 16 different samples from Dang, Chitwan, Nawalparasi, Sarlahi, Makwanpur and Rautahat districts of Nepal were obtained, representing honey of 4 different floral sources ‘Chiuri’ (Diploknema butyracea), ‘Rudhilo’ (Pogostemon plectranthoides), Mustard (Brassica napus), and Buckwheat (Fagopyrum esculentum). Chemical composition and bioactive components of the honey samples were studied.Moisture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The results showed that the 13 honey samples surveyed had HMF contents ranging from 0.049 to 2.933 mg/kg (Table 1). The CoffeeHC 3 sample had the highest HMF content (2.933 ± 0.022 mg/kg) but was still lower than the honey in Nepal (49.5 mg/kg) [30] or the honey from Melipona subnitida (7.56 mg/kg) and Apis mellifera (10.82 mg/kg) [11]. The contents of HMF in the honey samples were relatively low because the samples were analyzed immediately after being brought to the laboratory and the correct transportation and storage processes also maintained the honey as fresh samples.…”
Section: Physicochemical Parametersmentioning
confidence: 82%
“…The results showed that the 13 honey samples surveyed had HMF contents ranging from 0.049 to 2.933 mg/kg (Table 1). The CoffeeHC 3 sample had the highest HMF content (2.933 ± 0.022 mg/kg) but was still lower than the honey in Nepal (49.5 mg/kg) [30] or the honey from Melipona subnitida (7.56 mg/kg) and Apis mellifera (10.82 mg/kg) [11]. The contents of HMF in the honey samples were relatively low because the samples were analyzed immediately after being brought to the laboratory and the correct transportation and storage processes also maintained the honey as fresh samples.…”
Section: Physicochemical Parametersmentioning
confidence: 82%
“…But the Khoriya cultivation is decreasing in the present days (Mukul and Byg, 2020). (Bhattarai et al, 2019). Local people have been planting the Chiuri tree for the past many years.…”
Section: Households Involved In Bee Keepingmentioning
confidence: 99%
“…The extracts of the spices were prepared as described by Dimitrijević et al (2014) [26] and some modifications made by Bhattarai et al (2019) [27]. 5 g powdered spice was ground with 80 % methanol (30 mL) and was kept in an orbital shaker (Accumax, India) shaking continuously for about 20 minutes, and filtered through Whatman No.…”
Section: Phytochemical Analysismentioning
confidence: 99%